Malignant tumors in patients with end stage renal failure undergoing renal replacement therapy - Kade, Grzegorz; Lubas, Arkadiusz; Bodnar, Lubomir; Szczylik, Cezary; Wańkowicz, Zofia (Contemporary Oncology/Współczesna Onkologia, 2012)
In 1975 Matas and co-workers were the first in the world literature to show an increased risk of malignant tumor occurrence in the group of hemodialyzed patients and kidney transplant recipients. The report is an analysis of world literature from the last 35 years in reference to epidemiology as well as the profile of screening tests and diagnostic methods related to malignant tumors in the population with end stage renal disease, especially hemodialyzed patients.